An economic analysis of producing grain and biomass in Kansas - Brammer, Jon (Kansas State University, 2014)
This study examines the net returns from grain and biomass production from seven annual crop rotations using six different management scenarios. This study also examines the profitability of producing biomass from three perennial crops using four management scenarios. Soybeans were rotated with grain sorghum, dual purpose sorghum, photoperiod sensitive sorghum, brown mid-rib (BMR) sorghum, and corn. Continuously cropped corn was also included. Perennial grasses including switchgrass and big bluestem were compared to a traditional crop, alfalfa. Yields and input data for the crops was from an experimental field study conducted at Kansas State University, Manhattan KS. Enterprise budgets were constructed for rotations of five sorghum varieties with soybeans, corn and soybeans, and continuous corn. Enterprise budgets were also constructed for three perennial crops; consisting of switchgrass, big bluestem grass, and alfalfa. Perennial crop costs and returns are estimated over an assumed 10 year production horizon. Costs and net returns for each of these budgets were compared to determine which crop rotation was the most economically feasible. Yield and input rates, excluding soybean yield and inputs, used were collected from an agronomic field experiment at Manhattan located in Riley County, Kansas (Propheter, 2009; Roozeboom et al., 2011). Costs of inputs were from USDA Agricultural Prices, Kansas State University farm management guides, and Sharpe Brothers Seed Company. Harvest costs are from Kansas State University farm management guides and a Northeastern Colorado and Northwestern Kansas producer survey. The corn- soybean rotation had the highest net returns per acre across all annual crop scenarios. The corn-soybean rotation did not have the highest net returns per acre when an alternative price was used for the photoperiod sensitive sorghum-soybean rotation. The dual purpose sorghum-soybean rotation had the second highest net returns per acre across all annual crop scenarios. The corn-soybean and dual purpose sorghum-soybean rotations had high grain net returns, and low to average biomass production costs. Alfalfa had the highest amortized net returns of the perennial crops, and had positive establishment year net returns. Alfalfa had higher amortized net returns and establishment year net returns than switchgrass and big bluestem.
Keywords: Biomass; Economics; Farm Management; Agricultural (0503)